Complications of Fracture Treatment by Traditional Bonesetters in West Java, Indonesia - Putri Liana Warman; Yoyos Dias Ismiarto; Undang Ruhimat (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Traditional medicine practices are still occurring especially in developing countries such as Indonesia. One of the traditional practitioners is the traditional bonesetter (TBS). Due to lack of knowledge of human anatomy, physiology, infection prevention and control, the practices of the TBS has a risk to increase the complications in fractured patients. The objectives of this study was to identify the complications of fractured patients treated by the TBS who were admitted to dr. Hasan Sadikin General Hospital in West Java, IndonesiaMethods: This descriptive study involved 86 medical records of fractured patients admitted to the hospital, from January to December 2014. The collected data were gender, age, admission time after occurrence of the fracture, site of the fracture and early or delayed complications. Moreover, those data were analyzed and presented using frequency tabulation. Results: Out of 86 patients; 61 (70.93%) were males; 16 (18.60%) were 21–30 years old; 25 (29.07%) had fractures 1–3 months before admitted to the hospital; 83 (96.51%) had closed fractures. There were 86 patients with 109 fractures location; 66 (76.74%) had fractures in one location; 41 (37.61%) had femoral fractures. Half of the patients had malunion.Conclusions: The most complication is malunion.